Correlation between composition, structure and properties of poly(lactic acid) / polyadipate based nanobiocomposites - Martino, Veronica P. (2010)
Poly(lactic acid) plasticized with 15 and 20 wt.-% of polyadipate was melt-blended with different amounts of an O-MMT (1–5 wt.-%) to prepare nano-biocomposites. The effect of plasticizer and nanofiller contents on the morphology and on thermal, mechanical and barrier properties of PLA-based nano-biocomposites was evaluated in order to understand their structure-properties relationships. The oxygen transmission rate was notably reduced (around 45%) with increasing amount of clay due to an increased tortuosity. However, for clay concentrations above 3 wt.-%, a significant detriment in ductile properties could also be observed. For a given amount of nanofiller, the increasing plasticizer concentration improved the clay dispersion through the polymeric matrix.